A comparative study to evaluate milligan morgan hemorrhoidectomy versus pile suture method in management of haemorrhoids - ., Aditya; Raj, Kuldeep; Agarwal, P. N.; Nasar, Md Abu (International Surgery Journal, 2021)
Background: A pile suture technique was described originally by the Farag in 1978 was better in terms of post- operative pain, bleeding, hospital stay and early return to work which are the distressing effects of conventional Milligan Morgan Hemorrhoidectomy which is well accepted surgical procedure for haemorrhoids. This study is designed to compare the pile suture and Milligan Morgan Hemorrhoidectomy. Methods: After fulfilling the criteria, 60 patients were randomly allocated to the group A (Pile Suture [PS] n -30) and group B (Milligan Morgan Hemorrhoidectomy [MM] n – 30). The techniques were evaluated with respect to the operative time, pain scores, bleeding, hospital stay, return to work, and recurrence. Results: The mean age of patients was 44.33 years and 42.77 years in the pile suture group and MM group respectively. Grade III or IV hemorrhoids were more common in men (i.e., 80% and 60% in the pile suture and MM group, respectively). The mean operative time was shorter in the PS 20.10 minutes versus 51.47 minutes in the MM group (P .001). The bleeding and pain scores were less in the PS. Mean hospital stay was 4 days and 6.6 days in the PS and MM group, respectively. The patients in the pile suture group returned to their routine activities earlier (i.e., within 7.33 days) as compared with 16.87 days in the MM group. Conclusions: Therefore, pile suture method can be considered as less traumatic for the patients and method can be recommended as a safer alternative to Milligan Morgan haemorrhoidectomy.